Universities as Drivers of Social Innovation: Theoretical Overview and Lessons from the "campUS" Research - Fassi, Davide; Landoni, Paolo; Piredda, Francesca; Salvadeo, Pierluigi (Research for development, 2020)
Reviews the social role of universities in the urban context Covers themes and models of major interest Explains how to ensure a legacy of grassroots initiatives
Keywords: Mise en valeur; Réservé UdeM; Rôle des universités